Efektivitas Gerakan Senam Dasar dalam Meningkatkan Konsentrasi Belajar Siswa - Lubis, M. Anwar Azhari; Panjaitan, Afni Rahma Sagita; Nasution, Syahril Ramadhan; Suyono, Suyono (Lembaga Yasin AlSys, 2024)
Study concentration is the ability to concentrate the mind on the learning process, or focus on learning, very important for students because it supports better understanding and good memory. The aim of this research is to find out how effective basic gymnastics is in increasing children's learning concentration. This research is qualitative and descriptive. Data collection techniques use observation, interviews and documentation. Based on the research results, it can be concluded that this exercise can increase blood flow to the brain, improve cognitive function, and reduce stress and anxiety. Basic gymnastic movements can help children become more focused, disciplined and organized when completing school assignments. Basic gymnastics also helps children learn social and emotional skills such as cooperation and self-control, which are very useful when studying in the classroom. Doing basic exercises regularly provides a boost that can help children overcome boredom and stay focused during class. Thus, elementary gymnastics is a great and fun way to improve students' concentration in elementary school.